Novel macromolecules in food systems - Doxastakis, George; Kiosseoglou, V. (Vassilios) (Developments in food science, 2000)
Applying recent advances in biological and physical sciences, food scientists have created "novel food ingredients" enzymatically, chemically or microbiologically. Chief among these are "novel proteins and polysaccharides" which, like the more established traditional macromolecules, can perform multifunctional roles such as thickening, stabilization, gelation or encapsulation and in this way determine to a large extent the shelf life, texture and nutritional value of natural and processed foods. Featuring the latest advances on chemistry, structure and functional properties of "novel proteins and polysaccharides", with an emphasis on fundamental structure-function relationships, this book will be valuable to all those working in product development and fundamental food research